Discrete multi-objective optimization of particle swarm optimizer algorithm for multi-agents collaborative planning - Xiao-bo SHI; Yin ZHANG; Shan ZHAO; Deng-ming XIAO (Tongxin xuebao)
Although multiple mobile agents(MA)collaboration can quickly and efficiently complete data aggregation in wireless sensor network,the MA carrying data packages extensively increase along with a raise in the number of data source nodes accessed by MA,which causes unbalanced energy load of sensor nodes,high energy consumption of partial source nodes,and shortened lifetime of networks.The existing related works mainly focus on the objective of decreasing total energy consumption of multiple MA,without considering that rapidly energy consumption of partial source nodes has a negative effect on networks lifetime.Therefore,discrete multi-objective optimization of particle swarm algorithm was proposed,which used the total network energy consumption and mobile agent load balancing as fitness function for the approximate optimal itinerary plan in multiple mobile agent collaboration.Furthermore,the simulation result of the proposed algorithm is better than the similar algorithm in total energy consumption and network lifetime.